The detailed clinical objectives approach to designing clinical trials and choosing estimands. (20th May 2021) - Bell, James; Hamilton, Alan; Sailer, Oliver; Voss, Florian
Abstract: Objective setting is a necessary early step in the development of a clinical trial. ICH E9(R1) notes that the clinical objectives of a trial lead directly to the choice of estimands but barely discusses objectives themselves. Indeed, there is very little guidance anywhere in literature about objectives in clinical trials. This article identifies the substantial overlap between description of estimands and high quality definitions of objectives. It consequently shows that the estimand is decided by the precise choice of trial objective, and that therefore estimand decisions should be made at the objective level. The Detailed Clinical Objectives approach is proposed to support this. It emphasises clarity, specificity and a clinical focus when choosing and documenting objectives. Template text and examples are included to provide guidance on how it can be used in real trials. Finally, we describe objective‐driven trial design, emphasising how strong objective setting establishes an important foundation for rigorous trial design discussions, logistical and operational decision‐making during trial preparations, and clear communication of results and conclusions at the end of the trial. Highlighting the distinctions between objectives and estimands, we note how an objective‐based framework can build on the ICH E9(R1) estimand framework to address many of its unanswered questions.